The Role of Transformational, Transactional, and Ethical Leadership for Fostering Employee Motivation in Nepal - Narayan Prasad Aryal,; Padam Bahadur Lama,; Rohan Shrestha, (Interdisciplinary Journal of Management and Social Sciences, 2024)
The aim of this research is to investigate the effects of three different leadership styles; transformational, transactional, and ethical on the work motivation of Nepalese banking sector employees. As theoretical gap existed in the previous research, this study attempt to contribute to this theoretical gap. The structured questionnaire for survey was developed and disseminated among the target employees of commercial and development banks existed in Kathmandu.  Similarly, Out of 160 questionnaire distributed, researcher received only 140 useable data. Thus, cross-sectional data used for collecting data adopting convenience-sampling technique.   The research findings revealed that leadership styles consisting of transformational, transactional, and ethical leadership depicted a positive and significant impact on employee work motivation among the employees of banks in Nepal. The findings of the study stands as a benchmark for leaders, policy makers, academician and others for decision making.